Microgrid design and operation : toward smart energy in cities - Delfino, Federico; Procopio, Renato; Rossi, Mansueto; Brignone, Massimo; Robba, Michela; Bracco, Stefano (Artech House, 2018)
With the growth of renewable energy sources, microgrids have become a key component in the distribution of power to localized areas while connected to the traditional grid or operating in a disconnected island mode. Based on the extensive real-world experience of the authors, this cutting-edge resource provides a basis for the design, installation, and day-by-day management of microgrids.nnProfessionals find coverage of the critical aspects they need to understand, from the initial planning and the selection of the most appropriate technologies and equipment, to optimal management and real-time control. Moreover, this forward-looking book places emphasis on new architectures of the energy systems of the future. Written in accessible language with practical examples, the book explains advanced topics such as optimization algorithms for energy management systems, control issues for both on-grid and island mode, and microgrid protection. Practitioners are also provided with a complete vision for the deployment of the microgrid in smart cities. Publisher abstract.
6.7.2 Installation Costs.
Keywords: Microgrids (Smart power grids); Electric power systems -- Technological innovations.; elektronické knihy; electronic books